Weight changes during chemotherapy for breast cancer - Costa, Luciano José Megale; Varella, Paulo César Spotti; Giglio, Auro del (São Paulo Medical Journal, 2002)
CONTEXT: Patients receiving adjuvant chemotherapy for breast cancer have a tendency to gain weight. This tendency has determining factors not completely defined and an unknown prognostic impact. OBJECTIVE: To evaluate weight change during chemotherapy for breast cancer in a defined population and to identify its predisposing factors and possible prognostic significance. DESIGN: Observational, retrospective cohort study. SETTING: Private clinical oncology service. PARTICIPANTS: 106 consecutive patients with breast cancer treated between June 1994 and April 2000, who received neoadjuvant (n = 8), adjuvant (n = 74) or palliative (n = 24) chemotherapy. INTERVENTION: Review of medical records and gathering of clinical information, including patients’ body weights before treatment and at follow-up reviews. MAIN MEASUREMENTS: Body weight change, expressed as percentage of body weight per month in treatment; role of clinical data in weight change; and influence of weight change in overall survival and disease-free survival. RESULTS: There was a mean increase of 0.50 ± 1.42% (p = 0.21) of body weight per month of treatment. We noted a negative correlation between metastatic disease and weight gain (r = -0.447, p < 0.0001). In the adjuvant and neoadjuvant therapy groups there was a mean weight gain of 0.91 ± 1.19 % (p < 0.00001) per month, whereas in the metastatic (palliative) group, we observed a mean loss of 0.52 ± 1.21% (p = 0.11) of body weight per month during the treatment. We did not observe any statistically significant correlation between weight changes and disease-free survival or overall survival. CONCLUSIONS: Women with breast cancer undergoing adjuvant or neoadjuvant chemotherapy gain weight, whereas metastatic cancer patients will probably lose weight during palliative chemotherapy. Further studies are needed in order to evaluate the prognostic significance of weight changes during chemotherapy.